Bunga Teratai Sebagai Ide Penciptaan Karya Seni Grafis - Suci Rahmayani; Yofita Sandra (Lembaga Pengembangan Kinerja Dosen, 2023)
The final work aims to introduce the form of water lily as an ornamental water plant into graphic artworks by visualizing the shape of flower figures, animals, and other supporting objects found in lotus flowers.There are several stages carried out in accordance with the method used in the creation of the work, namely: Preparation is an observation related to the initial idea of the author's interest, Elaboration is the stage of exploring and displaying the beauty of lotus flowers reviewed from the internet, a collection of images and field surveys, Synthesis is the stage of starting to design how the work will be made in accordance with the title, Concept realization is the stage of the work process and completion is the final stage in the work.The results achieved in the creation of graphic art works are entitled